The complex origin of the Bosnian ocaklık timar - Moačanin, Nenad (Array, 2009)
In Bosnia, first the tax-free inheritable holdings of Vlach leaders, or their baştines, usually of small size, were simply proclaimed “timars”. This process was completed about 1530. Parallel to that, in many groups related by blood (ocak zadeleri) inheritance of sipahi grants according to the customary law became widespread, uninhibited by Ottoman authorities. In periods of crisis, imperial orders were issued where the locution “ocaklık timar” appears. The two types merged together to a large extent, soon to be joined by the third one, that is, the militia in fortresses, paid thru gedik or cash ocaklık.